Enhancement of the biodegradability of grain distillery wastewater to improve upflow anaerobic sludge blanket reactor efficiency - Gie, Lowna-Marie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2007.